Impact of Entrepreneurship Education on Entrepreneurial Intentions of Students: A review of empirical research - Zdolšek, Tanja; Širec, Karin (Naše gospodarstvo/Our economy, 2014)
The youth unemployment rate in the EU has been growing for many years, which is why the youth represent the priority group in the employment policy. Entrepreneurs create many jobs, so the acquisition of entrepreneurial competencies and positive entrepreneurial intentions through entrepreneurship education has significant importance. This paper provides an overview of empirical studies focused on the impact of entrepreneurship education on the entrepreneurial intentions of students in tertiary education from a socio-psychological perspective, using the theory of planned behaviour. The paper concludes with a layout of a research model to determine the impact of entrepreneurship education on students’ entrepreneurial competenci- es and intentions.